Social Impact Assessment of Croatian Railway Reforms - World Bank (2015)
In Croatia, initial steps to reform the railway sector date back to the middle of the first decade of the 2000s, with the formation of Croatian railways as a holding company. To help with further reforms of the Croatian railway sector, over the period 2011-2013, the World Bank was engaged in dialogue with the Croatian Government and the Croatian railway companies which resulted in a Croatian railway policy note. The poverty and social impact analysis (PSIA) is an analysis of the intended and unintended consequences of policy reforms on the wellbeing or welfare of different social groups, with particular focus on the poor and vulnerable. PSIA offers a set of analytical and process tools that: (a) determine distributional impacts to improve the analytical underpinnings of policy making; and (b) engage appropriate stakeholders in the policy-making process. The report is divided into following sections: first section gives executive summary. The introduction provides information on the economic situation in Croatia, including unemployment rates and pensions, the situation of the railway sector, and data on the restructuring process of the Croatian railways companies in second section. The third section contains the results obtained from the group discussions and in-depth interviews which are divided into four parts: the circumstances upon leaving the railway companies, after leaving, transferring to a new workplace, and the broader impacts on the community, including the impacts of closed and reduced lines. The last part of the section contains recommendations based on the obtained results.